Swine Gut Lactic Acid Bacteria and Their Exopolysaccharides Differentially Modulate Toll-like Receptor Signaling Depending on the Agave Fructans Used as a Carbon Source - Enrique A. Sanhueza-Carrera; Cynthia Fernández-Lainez; César Castro-De la Mora; Daniel Ortega-Álvarez; Claudia Mendoza-Camacho; Jesús Manuel Cortéz-Sánchez; Beatriz Pérez-Guillé; Paul de Vos; Gabriel López-Velázquez (Animals)
Exopolysaccharides (EPSs) produced by probiotic bacteria have garnered attention due to their effects on the gut health of humans and animals. The nutrients that probiotics access during their growth are essential for producing beneficial effects on host health. Direct immunomodulatory effects of graminan-type fructans (GTFs) from Agave tequilana through toll-like receptors (TLRs) have been demonstrated. However, the immunomodulatory effects of these fructans, mediated through the EPSs produced by the probiotics cultivated with them, remain unexplored. We explored the immunomodulatory effects of lactic acid bacteria (LAB) strains isolated from swine and their EPSs, based on the GTFs used as carbon sources during their growth. While the LAB strains activated the NF-κB pathway independently of the GTF source, their EPSs activated it in a GTF source-dependent manner. LAB activation through TLR2 showed a GTF source dependency, whereas their EPSs activated TLR2 independently of the GTF source. The LAB and their EPSs activated TLR4 in a GTF source-dependent manner. Both the LAB and their EPSs inhibited the activation of TLR2 and TLR4 agonists, which exhibited a strong dependence on the GTF source. The strength of GTF C’s immunomodulatory effects on LAB illustrates its specificity, its impact on the EPS structure, and its biological effects. Our results support the promising health benefits of this synbiotic model for swine health and lowering inflammation.